PsycEXTRA Dataset 2007
DOI: 10.1037/e741552011-005
|View full text |Cite
|
Sign up to set email alerts
|

Looking Toward the Future: Predicting Retirement Satisfaction

Abstract: ~Many retirees experience a decrease in life satisfaction after retirement. One explanation for the dissatisfaction is that retirement was not as one had expected (i.e., feelings about retirement were inaccurately predicted). Planning for retirement involves predicting aspects of retirement and making decisions accordingly. The present study used a between subjects design to examine the predicted feelings of workers regarding their retirement expectations compared to the actual feelings of retired workers. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Previous studies have identified a range of factors which contribute to retirement satisfaction including human capital (Fouquereau, Fernandez, Fonseca, Paul, & Uotinen, 2005; Heybroek, Haynes, & Baxter, 2015; Noone, Stephens, & Alpass, 2009; Potočnik et al., 2013), social resources (Price, 2003; Price & Nesteruk, 2015), environmental resources (Moffatt & Heaven, 2017), psychological factors (Barbosa, Monteiro, & Murta, 2016; Price & Balaswamy, 2009; Taylor, Goldberg, Shore, & Lipka, 2008; van Solinge &Henkens, 2005), and characteristics of former work or the circumstances of withdrawal from the labor market (De Vaus, Wells, Kendig, & Quine, 2007; Muratore & Earl, 2015; van Solinge & Henkens, 2008; Wang, 2007). Retirement planning and the setting of goals have also been identified as important contributors to retirement satisfaction, adjustment, and well-being (Adams & Rau, 2011; Barnes & Parry, 2004; Curl & Ingram, 2013; Davis, 2007; Hewitt et al., 2010; Reitzes & Mutran, 2004; Topa, Moriano, Depolo, Alcover, & Morales, 2009). In some cases, planning factors have been identified as the largest contributors to satisfaction and health in retirement (Moffatt & Heaven, 2017; Noone et al., 2009; Schellenberg, Turcotte, & Ram, 2005; Zhu-Sams, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have identified a range of factors which contribute to retirement satisfaction including human capital (Fouquereau, Fernandez, Fonseca, Paul, & Uotinen, 2005; Heybroek, Haynes, & Baxter, 2015; Noone, Stephens, & Alpass, 2009; Potočnik et al., 2013), social resources (Price, 2003; Price & Nesteruk, 2015), environmental resources (Moffatt & Heaven, 2017), psychological factors (Barbosa, Monteiro, & Murta, 2016; Price & Balaswamy, 2009; Taylor, Goldberg, Shore, & Lipka, 2008; van Solinge &Henkens, 2005), and characteristics of former work or the circumstances of withdrawal from the labor market (De Vaus, Wells, Kendig, & Quine, 2007; Muratore & Earl, 2015; van Solinge & Henkens, 2008; Wang, 2007). Retirement planning and the setting of goals have also been identified as important contributors to retirement satisfaction, adjustment, and well-being (Adams & Rau, 2011; Barnes & Parry, 2004; Curl & Ingram, 2013; Davis, 2007; Hewitt et al., 2010; Reitzes & Mutran, 2004; Topa, Moriano, Depolo, Alcover, & Morales, 2009). In some cases, planning factors have been identified as the largest contributors to satisfaction and health in retirement (Moffatt & Heaven, 2017; Noone et al., 2009; Schellenberg, Turcotte, & Ram, 2005; Zhu-Sams, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In essence, underlying mechanisms are poorly understood (Muratore & Earl, 2015; Taylor & Doverspike, 2003). One reason for this gap may be that most studies about retirement adjustment have not been conducted through a prospective longitudinal approach but rather based on retrospective recall (Davis, 2007; Principi et al., 2016). To fill this gap in knowledge, this study aims to investigate longitudinally the impact of thwarted and fulfilled plans on retirement satisfaction, and the main barriers to plan fulfillment, to assess how people adapt to unexpected retirement circumstances.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation